2022
DOI: 10.1186/s13049-022-00992-9
|View full text |Cite
|
Sign up to set email alerts
|

Maximum movement and cumulative movement (travel) to inform our understanding of secondary spinal cord injury and its application to collar use in self-extrication

Abstract: Background Motor vehicle collisions remain a common cause of spinal cord injury. Biomechanical studies of spinal movement often lack “real world” context and applicability. Additional data may enhance our understanding of the potential for secondary spinal cord injury. We propose the metric ‘travel’ (total movement) and suggest that our understanding of movement related risk of injury could be improved if travel was routinely reported. We report maximal movement and travel for collar applicatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…In healthy volunteers using cervical collars during vehicle and subsequent self‐extrication, collar use resulted in decreased maximal movement, a valuable surrogate measure for the risk of secondary SCI 31 . Maximal movements were found to be significantly decreased when a collar was used, while smaller movements still occurred resulting in comparable cumulative movement 31 . Although rescue services and medical providers operate with the rationale that smaller movements pose less risk for secondary spinal injury than larger movements, the effect of cumulative movement on SCI risk remains unknown.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In healthy volunteers using cervical collars during vehicle and subsequent self‐extrication, collar use resulted in decreased maximal movement, a valuable surrogate measure for the risk of secondary SCI 31 . Maximal movements were found to be significantly decreased when a collar was used, while smaller movements still occurred resulting in comparable cumulative movement 31 . Although rescue services and medical providers operate with the rationale that smaller movements pose less risk for secondary spinal injury than larger movements, the effect of cumulative movement on SCI risk remains unknown.…”
Section: Resultsmentioning
confidence: 99%
“…31 Maximal movements were found to be significantly decreased when a collar was used, while smaller movements still occurred resulting in comparable cumulative movement. 31 Although rescue services and medical providers operate with the rationale that smaller movements pose less risk for secondary spinal injury than larger movements, the effect of cumulative movement on SCI risk remains unknown. Another study found that there was a significantly increased average movement of the cervical spine with cervical collar use during self-extrication than without.…”
Section: Impact On Restricting Movementmentioning
confidence: 90%
“…This study reinforces emerging guidelines previously discussed supporting the removal of systematic cervical collars use from first-aid protocols to save critical time [ 7 , 9 11 , 30 , 52 , 53 ]. A recent study on maximum movement and cumulative movement of the head measured with IMUs during MVA self-extrications simulation showed that total travel motion is similar across self-extricating healthy volunteers with and without a collar [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Maximum excursions (movement from a hypothetical midline) were calculated for anterior/posterior (AP) and lateral (LR) movement of the cervical and lumbar spine, respectively. In addition to reporting maximum excursions (the single largest movement) we report "travel" -the cumulative total of all movements throughout the extrication [18] .…”
Section: Methodsmentioning
confidence: 99%